The impact of support from emergency nurse organizations on compassion fatigue: the mediating role of psychological capital - Daixun Xie; Xiaoqin Zhu; Xiurong Zhang; Zhaoquan Jiang; Tao Liu (Frontiers in Public Health)
BackgroundWith ongoing healthcare system reforms in China and escalating demands for emergency services, emergency nurses frequently face high-pressure, complex work environments. This increases their psychological burden. Additionally, limited healthcare resources at the grassroots level and high workloads heighten their vulnerability to compassion fatigue. Current research into the interplay between psychological capital, perceived organizational support, and compassion fatigue among emergency nurses is limited, particularly regarding the mediating role of psychological capital.ObjectiveThis study aims to explore the relationship between organizational support, psychological capital, and compassion fatigue among emergency nurses. It specifically investigates the mediating role of psychological capital in the relationship between organizational support and compassion fatigue.MethodsA total of 466 emergency nurses from medical institutions in the Chengdu-Chongqing area were selected through convenience sampling. Data were collected using the Psychological Capital Questionnaire, the Sense of Organizational Support Scale, and the Compassion Fatigue Scale. The correlations among these variables were analyzed using SPSS 26.0, and the mediating effects were tested using AMOS 26.0.ResultsThere is a significant negative correlation between psychological capital and compassion fatigue among emergency nurses (r = −0.309, P < 0.01), as well as between organizational support and compassion fatigue (r = −0.449, P < 0.01). Psychological capital acts as a partial mediator in the relationship between organizational support and compassion fatigue, with a mediating effect value of −0.169, accounting for 27% of the total effect.ConclusionThe findings indicate a significant association between psychological capital, perceived organizational support, and compassion fatigue among emergency nurses, with psychological capital playing a mediating role. Enhancing psychological capital and perceived organizational support for emergency nurses is an effective strategy for managing emotional stress at work. Healthcare institutions should implement targeted interventions to improve nursing service quality and promote the sustainable development of the nursing profession.